Penerapan Sistem Manajemen Keselamatan dan Kesehatan Kerja Untuk Peningkatan Pelayanan Terminal Purabaya Berdasarkan PP No. 50 Tahun 2012 - Akbar Bayu Kresno Suharso; Andaryati Andaryati; Nia Saurina (Jurnal Manajemen Teknologi & Teknik Sipil, 2022)
The situation in the field shows that there is still a high number of work accidents that occur in transportation facilities. It is very unfortunate if the Purabaya Terminal has not fully implemented the Occupational Safety and Health Management System (SMK3) which will have a positive impact on service quality, operations and performance by making efficient and effective efforts to prevent the risk of work-related accidents and diseases. If this happens, it can improve customer and community relations which aim to increase community satisfaction. This is in line with PP No. 50 of 2012. The purpose of this study was to describe the success rate of OSHM implementation at Purabaya Terminal based on PP no. 50 of 2012 and analyze the inhibiting factors. This research method uses a qualitative method by collecting survey data using a checklist questionnaire instrument and interviewing the entire study population, namely all employees at the Purabaya Terminal. After data collection, an analysis of the achievement level of OSHM implementation at the Purabaya terminal was carried out with a result of 27% of 166 criteria. This figure indicates a low rating of the application. Factors that influence this include the lack of staff in the OSH control section, lack of funds, lack of OSH awareness, and inadequate and uneven facilities. So that by implementing these results, it can be used to continue K3 pre-implementation activities in the form of training, outreach and providing OSH awareness to all employees at Purabaya Terminal.